2017
DOI: 10.1371/journal.pone.0179352
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of tablet-based software for the detection of concussion

Abstract: Despite the high prevalence of traumatic brain injuries (TBI), there are few rapid and straightforward tests to improve its assessment. To this end, we developed a tablet-based software battery ("BrainCheck") for concussion detection that is well suited to sports, emergency department, and clinical settings. This article is a study of the diagnostic accuracy of BrainCheck. We administered BrainCheck to 30 TBI patients and 30 pain-matched controls at a hospital Emergency Department (ED), and 538 healthy individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 29 publications
5
30
0
1
Order By: Relevance
“…To assess the communication between brain areas for movement control, our group developed a touch screen based functional assessment tool using a visuomotor task that incorporates two forms of non-standard mapping: explicit rule integration (strategic control), and implicit spatial vision-to-hand-motion realignment (sensorimotor recalibration). Portable software applications to assess brain function following injury are increasingly being developed, and offer a useful, pragmatic approach to providing information to the user and their caregivers (18)(19)(20)(21)(22). In our task, a basic standard mapping condition has the participant place their finger over a central start target on a vertical touch screen, immediately slide their finger on that same screen directly toward a target that appears, and hold it there.…”
Section: A Failure To Communicate: the Effect Of Mild Brain Injury Onmentioning
confidence: 99%
“…To assess the communication between brain areas for movement control, our group developed a touch screen based functional assessment tool using a visuomotor task that incorporates two forms of non-standard mapping: explicit rule integration (strategic control), and implicit spatial vision-to-hand-motion realignment (sensorimotor recalibration). Portable software applications to assess brain function following injury are increasingly being developed, and offer a useful, pragmatic approach to providing information to the user and their caregivers (18)(19)(20)(21)(22). In our task, a basic standard mapping condition has the participant place their finger over a central start target on a vertical touch screen, immediately slide their finger on that same screen directly toward a target that appears, and hold it there.…”
Section: A Failure To Communicate: the Effect Of Mild Brain Injury Onmentioning
confidence: 99%
“…A short description of each of the 5 assessments that make-up the BrainCheck battery (V4.0.0) is listed in Table 1. More detailed descriptions may be found in a previous validation study [24] . After completion of the BrainCheck battery, the score of each assessment is calculated using assessment specific measurements by the BrainCheck software (shown in Table 1).…”
Section: Measurementsmentioning
confidence: 99%
“…Prior studies have shown that some computerized cognitive tests demonstrate high accuracy in differentiating dementia patients from healthy participants, but do not have adequate psychometrics to distinguish MCI from dementia [19][20][21][22] . Ideally, computerized cognitive tests would aim to be more rapid and maximize accessibility to This study evaluated BrainCheck, a computerized cognitive test battery previously validated for its diagnostic accuracy for the detection of concussion [24] and dementia-related cognitive decline [25] . BrainCheck is portable, allows for self and remote administration, and can be reimbursed by insurance plans in the US.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BrainCheck Sport is a computerized neurocognitive test available on iPad, iPhone, or a desktop browser and was previously validated for its diagnostic accuracy for the detection of concussion [22]. BrainCheck Memory is a modified version of this program that targets dementia-related cognitive decline.…”
Section: Introductionmentioning
confidence: 99%